2003
DOI: 10.1177/0891241603032003003
|View full text |Cite
|
Sign up to set email alerts
|

The Dialectical Gaze

Abstract: Much of past research on female exotic dance has characterized strippers as deviant workers who are either passive, objectified victims of a sexploitation system that trades on their bodies for financial gain or as active subjects who work the exchange for their own benefit. Drawing on theories of power, performance, and communication, this work complicates the subject-object tension, showing how power circulates through a system of competing discursive relationships forming a dialectic of agency and constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…For instance, some studies suggest that being seen as an object can have a negative effect on female dancers' self-views (Barton 2007;Boles and Garbin 1974;Bradley-Engen and Ulmer 2009;Murphy 2003;Ryan and Martin 2001;Wesely 2002). For instance, Barton (2007) found that strip clubs that regularly held "contests" where women were judged and rejected based on their body put their selfconcept in a precarious position.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, some studies suggest that being seen as an object can have a negative effect on female dancers' self-views (Barton 2007;Boles and Garbin 1974;Bradley-Engen and Ulmer 2009;Murphy 2003;Ryan and Martin 2001;Wesely 2002). For instance, Barton (2007) found that strip clubs that regularly held "contests" where women were judged and rejected based on their body put their selfconcept in a precarious position.…”
Section: Discussionmentioning
confidence: 93%
“…Dancers confront competing feelings of empowerment and exploitation (Deshotels and Forsyth, 2006;Sanders and Hardy, 2011;Wood, 2000) and of shame / guilt and honour / pride (Bradley, 2006;Murphy, 2003) and contradictory expectations of performing erotic labour well (to be sexy, arouse others) and societal norms of female exclusivity and male sexual privilege (Bradley, 2007). The lived experiences of dancers involved in this study reveal an awareness of the social and moral taint associated with the work and their self-identities.…”
Section: Discussionmentioning
confidence: 99%
“…We look to a particular type of dirty work, namely exotic dancing because it has been categorised as a high-breadth high-depth stigmatised occupation (Kreiner, Ashforth and Sluss, 2006) and the experience of ambivalence, contradiction and ambiguity is likely to be particularly salient for those who perform this type of work (Bradley, 2007;Deshotels and Forsyth, 2006;Murphy, 2003;Sanders and Hardy, 2011). Dancers confront competing feelings of empowerment and exploitation (Deshotels and Forsyth, 2006;Sanders and Hardy, 2011;Wood, 2000) and of shame / guilt and honour / pride (Bradley, 2006;Murphy, 2003) and contradictory expectations of performing erotic labour well (to be sexy, arouse others) and societal norms of female exclusivity and male sexual privilege (Bradley, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the tradition of the many observational studies investigating the effect of interactional cues on tipping behaviours (Stier and Hall 1984) where participants 'require autonomy and secrecy'. This conclusion is supported by the experiences reported by scholars who have chosen to undergo their research openly (Bradley 2007;Brooks 2010;Montemurro, et al, 2003;Montemurro 2001;Murphy 2003;Spivey 2005;Thompson, et al, 2003). In these cases there have been reports of difficulties with fieldwork in order to remain unobtrusive (Montemurro, Bloom and Madell 2003) or having access restricted to certain areas (Thompson, et al, 2003).…”
Section: Covert Researchmentioning
confidence: 83%